1999
DOI: 10.1046/j.1464-5491.1999.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the amylin analogue pramlintide on hepatic glucagon responses and intermediary metabolism in Type 1 diabetic subjects

Abstract: Co-administration of pramlintide and insulin to Type 1 diabetic subjects for 4 weeks does not change the plasma glucose or endogenous glucose production response to a glucagon challenge, following an overnight fast. In addition, pramlintide administration does not appear to alter insulin-mediated glucose disposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
(76 reference statements)
0
7
2
Order By: Relevance
“…Moreover, a relationship between amylin and glucagon has been hypothesized from studies investigating the dynamics of amylin or its agonist pramlintide after their administration [8,9,25]. However, only the results of the present study confirm for the first time the role of endogenous amylin in the modulation in dynamic conditions of postprandial glucagon secretion in human subjects and therefore a physiological role for amylin in glucose homeostasis, possibly through this modulation of glucagon secretion.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, a relationship between amylin and glucagon has been hypothesized from studies investigating the dynamics of amylin or its agonist pramlintide after their administration [8,9,25]. However, only the results of the present study confirm for the first time the role of endogenous amylin in the modulation in dynamic conditions of postprandial glucagon secretion in human subjects and therefore a physiological role for amylin in glucose homeostasis, possibly through this modulation of glucagon secretion.…”
Section: Discussioncontrasting
confidence: 56%
“…Preclinical studies have shown that amylin slows nutrient absorption, acts as a satiety factor, and decreases glucagon secretion (86). In clinical studies in which pramlinitide (a commercially available amylin analog) was used as an adjunct to insulin therapy in patients with T1DM, there were decreases in plasma glucagon levels, glucose fluctuations, postprandial glucose levels, and plasma triglyceride concentrations (86)(87)(88)(89). As one might expect, the patients' insulin dose had to be decreased in order to prevent hypoglycemia.…”
Section: Noninsulin Glucagon Suppressorsmentioning
confidence: 99%
“…The amylinomimetic, pramlintide: (1) increases satiety, diminishes caloric intake, and reduces weight; [32][33][34][35][36][37][38] (2) has no evidence for diminished intestinal absorption; (3) delays gastric emptying; [39][40][41][42][43] (4) decreases glucagon secretion; [44][45][46] (5) reduces postprandial oxidative stress; 47 (6) has no apparent effect on PGU; 48 and (7) diminishes insulin requirements. 34 It would appear pramlintide would have the most profound effect on CE (decrease), HGU (decrease), GNG (decrease), and IR (decrease), while having modest to negligible effects on PGU and PIE.…”
Section: Glucose Supply and Insulin Demand Dynamics Of Newer Antidiabmentioning
confidence: 99%